A linear antenna array failure correction using improved bat algorithm. Issue 7 (28th April 2017) - Singh Grewal, Narwant; Rattan, Munish; Singh Patterh, Manjeet
Abstract: The failure of antenna array elements causes disturbance in the sidelobe power level. In this article, an improved flexible approach that use bat algorithm is proposed and applied to solve the problem of antenna array failure by controlling only the amplitude excitation of array elements. An adaptive inertia weight approach is applied to the standard bat algorithm to improve the quality of the solution and the speed of convergence. The effectiveness of the proposed improved bat algorithm (IBA) is verified on different standard test functions. Numerical examples of element failure correction are presented to show the capability of this flexible approach in antenna array failure correction.